PROSPECTS FOR THE APPLICATION OF BIODEGRADABLE MAGNESIUM ALLOYS IN MODERN REGENERATIVE MEDICINE (Ustozlar uchun, 2026)
analytical review of publications and dissertations from international databases, including PubMed, Scopus, and eLibrary, was conducted. The physicochemical properties of magnesium were investigated in comparison with traditional bioinert metals (titanium, stainless steel). Additionally, the results of recent trials of magnesium systems for maxillofacial surgery and traumatology were analyzed.